Annotation Between Formation And Information. Issue 2 (October 2017) - Leonhardt, Jürgen
Abstract : Between 1490 and 1525 various German print shops produced a great number of rather short texts that were the subject of university lectures as fascicles for students. Wide margins and line spacing left room for hand-written notes taken during the lecture course. Many of such annotated copies allow us to assume that the annotations are not textual commentaries in the usual sense. Rather, they are examples of a media practice indicating the tension between orality, handwriting, and printed books, especially since both the oral lecture course and the individual notes represent processes of transmitting and storing knowledge in which the text that is being explained does not even play a central role. We may compare them to modern, frequently collaborative practices that pursue aims going beyond straightforward models of text explication, which may help us develop more precise descriptions as well as a deeper understanding of the hermeneutics of textual annotation.